Thermoplastic resin composition and molded article using same

The thermoplastic resin composition, comprising specific copolymers, addresses the issue of friction noise in styrene-based resin products by reducing the coefficient of friction and minimizing stick-slip phenomena, enhancing both mechanical and optical properties for applications in electric vehicle interiors.

JP7671698B2Active Publication Date: 2025-05-02LOTTE CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021563008
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-27
Filing Date
2020-04-28
Publication Date
2025-05-02
Estimated Expiration
2040-04-28

AI Technical Summary

Technical Problem

Styrene-based resin molded products often exhibit friction noise when combined with other resin materials, particularly due to their high coefficient of friction, which can lead to stick-slip phenomena and discomfort in vehicles, especially in electric vehicles where noise levels are typically lower.

Method used

A thermoplastic resin composition is developed, comprising specific components such as polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer, acrylonitrile-butadiene-styrene graft copolymer, styrene-vinyl cyanide copolymer, α-methylstyrene-based copolymer, and acrylonitrile-butadiene-styrene copolymer resin, which work together to reduce friction noise, enhance mechanical properties, and provide low optical properties.

Benefits of technology

The thermoplastic resin composition effectively minimizes stick-slip phenomena and significantly reduces friction noise, making it suitable for applications like automobile interior materials, particularly in electric vehicles, while also offering improved mechanical and optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671698000004
    Figure 0007671698000004
  • Figure 0007671698000001
    Figure 0007671698000001
  • Figure 0007671698000002
    Figure 0007671698000002
Patent Text Reader

Abstract

The present invention relates to a thermoplastic resin composition containing 1 to 6 parts by weight of (E) a polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer, relative to 100 parts by weight of a base resin containing: (A) 20 to 30% by weight of an acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubbery polymer of 200 to 350 nm; (B) 10 to 30% by weight of a styrene-vinyl cyanide copolymer; (C) 30 to 50% by weight of an α-methylstyrene copolymer; and (D) 10 to 30% by weight of an acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubbery polymer of 1,000 to 5,000 nm; and a molded article using the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic resin composition and a molded article utilizing the same. [Background technology]

[0002] Styrene-based resins, such as acrylonitrile-butadiene-styrene copolymer (ABS) resin, are widely used in automobiles, home appliances, office equipment, and other applications due to their excellent moldability, mechanical properties, appearance, and secondary processability.

[0003] Molded products using styrene resins are widely used in various products that require painting or no painting, such as interior and exterior materials for automobiles.

[0004] However, if a molded product made of styrene-based resin is used in an area where it comes into contact with and rubs against other parts made of other resins, such as polyethylene or polyvinyl chloride, or lining sheets or foams made of chloroprene rubber, natural rubber, polyester, polyethylene, or the like, friction noise may be generated.

[0005] Because styrene-based resins are non-crystalline resins, they have a higher coefficient of friction than crystalline resins such as polyethylene, polypropylene, and polyacetal. For example, when they are combined with components made of other resins, such as air conditioning vents in automobiles or car audio buttons, the high coefficient of friction can cause a stick-slip phenomenon and produce frictional noises (squeaks).

[0006] In recent years, as the demand for electric vehicles, which generate relatively less noise when driven compared to conventional automobiles, increases, the above-mentioned friction noise has emerged as a major cause of impairing comfort and quietness during riding. Therefore, the reality is that there is a need to develop automobile interior materials with excellent friction noise reduction properties. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a thermoplastic resin composition having excellent friction noise reduction effect, mechanical properties, and low optical properties, and to provide a molded article using the same. [Means for solving the problem]

[0008] In order to achieve the above object, according to one embodiment of the present invention, there is provided a thermoplastic resin composition comprising 100 parts by weight of a base resin comprising: (A) 20 to 30% by weight of an acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm; (B) 10 to 30% by weight of a styrene-vinyl cyanide copolymer; (C) 30 to 50% by weight of an α-methylstyrene copolymer; and (D) 10 to 30% by weight of an acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm; and (E) 1 to 6 parts by weight of a polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer.

[0009] The acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer (A) of 200 to 350 nm may have a core-shell structure including a core made of a butadiene-based rubber polymer and a shell formed by graft polymerization of acrylonitrile and styrene onto the core.

[0010] The (A) rubber polymer may contain 40 to 70% by weight of the core based on 100% by weight of an acrylonitrile-butadiene-styrene graft copolymer having an average particle size of 200 to 350 nm.

[0011] The styrene-vinyl cyanide copolymer (B) may be a copolymer of a monomer mixture containing 60 to 80% by weight of styrene and 20 to 40% by weight of a vinyl cyanide compound.

[0012] The styrene-vinyl cyanide copolymer (B) may have a weight average molecular weight of 80,000 to 200,000 g / mol.

[0013] The (C) α-methylstyrene copolymer may be a copolymer of a monomer mixture containing 50 to 80% by weight of α-methylstyrene, 10 to 40% by weight of a vinyl cyanide compound, and 0 to 40% by weight of an aromatic vinyl compound.

[0014] In the above (C) α-methylstyrene-based copolymer, the aromatic vinyl compound is selected from the group consisting of styrene (excluding α-methylstyrene) substituted or unsubstituted with a halogen or an alkyl group having 1 to 10 carbon atoms, and combinations thereof, and the vinyl cyanide compound is selected from the group consisting of acrylonitrile, methacrylonitrile, fumaronitrile, and combinations thereof.

[0015] The (C) α-methylstyrene-based copolymer may be an α-methylstyrene-styrene-acrylonitrile copolymer.

[0016] The acrylonitrile-butadiene-styrene copolymer resin (D) having an average particle size of the rubber polymer of 1,000 to 5,000 nm may include a dispersed phase having a core-shell structure including a core made of a butadiene-based rubber polymer and a shell formed by graft polymerization of acrylonitrile and styrene onto the core, and a continuous phase of a styrene-acrylonitrile copolymer.

[0017] Based on 100% by weight of the acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the (D) rubber polymer of 1,000 to 5,000 nm, the dispersed phase of the core-shell structure may comprise 10 to 30% by weight, and the continuous phase of the styrene-acrylonitrile copolymer may comprise 70 to 90% by weight.

[0018] The polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer (E) may be one in which an aromatic vinyl-glycidyl (meth)acrylate copolymer is grafted onto a substituted or unsubstituted polyolefin main chain.

[0019] Based on 100% by weight of the (E) polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer, the copolymer may contain 70 to 95% by weight of the substituted or unsubstituted polyolefin and 5 to 30% by weight of the aromatic vinyl-glycidyl (meth)acrylate copolymer.

[0020] The substituted or unsubstituted polyolefin may be one or more selected from the group including polyethylene and ethylene-vinyl acetate copolymer.

[0021] The aromatic vinyl-glycidyl (meth)acrylate copolymer may be a styrene-glycidyl methacrylate copolymer.

[0022] The styrene-glycidyl methacrylate copolymer may be a copolymer of a monomer mixture containing 50 to 95% by weight of styrene and 5 to 50% by weight of glycidyl methacrylate.

[0023] The (E) polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer may be one or more selected from the group including polyethylene-styrene-glycidyl methacrylate graft copolymer and ethylene-vinyl acetate-styrene-glycidyl methacrylate graft copolymer.

[0024] The thermoplastic resin composition may further include at least one additive selected from a nucleating agent, a coupling agent, a filler, a plasticizer, a lubricant, a release agent, an antibacterial agent, a heat stabilizer, an antioxidant, an ultraviolet stabilizer, a flame retardant, an antistatic agent, a colorant, and an impact modifier.

[0025] Meanwhile, a molded article is provided using a thermoplastic resin composition according to one embodiment of the present invention. Effect of the Invention

[0026] The thermoplastic resin composition according to one embodiment of the present invention and a molded product using the same have excellent friction noise reduction effect, mechanical properties, and low optical properties, and are therefore widely applicable to molding of various products that are used with or without painting.

[0027] For example, a molded article using the thermoplastic resin composition according to one embodiment of the present invention can minimize the stick-slip phenomenon, and is therefore usefully applied in applications such as automobile interior materials, which require a large reduction in frictional noise, for example, interior materials for electric vehicles, etc. In addition, when the molded article is used, more advanced automobile interior materials can be provided due to the excellent low optical properties of the thermoplastic resin composition according to one embodiment. [Brief description of the drawings]

[0028] [Figure 1] Figure 1 shows a diagram of the basic principle of the VDA230-206. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, a detailed description of embodiments of the present invention will be given by way of example only, and the present invention is not limited thereby, as defined only by the appended claims.

[0030] In this specification, unless otherwise specified, the average particle size is the volume average diameter, and means the Z-average particle size measured using a dynamic light scattering analyzer.

[0031] According to one embodiment of the present invention, there is provided a thermoplastic resin composition comprising 100 parts by weight of a base resin comprising (A) 20 to 30% by weight of an acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm; (B) 10 to 30% by weight of a styrene-vinyl cyanide copolymer; (C) 30 to 50% by weight of an α-methylstyrene copolymer; and (D) 10 to 30% by weight of an acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm, and (E) 1 to 6 parts by weight of a polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer.

[0032] Hereinafter, each component contained in the thermoplastic resin composition will be specifically described.

[0033] (A) An acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm. In one embodiment, the acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm imparts excellent impact resistance to the thermoplastic resin composition. In one embodiment, the acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm may have a core-shell structure in which a central portion (core) is made of a butadiene-based rubber polymer component and a shell is formed by graft polymerization reaction of acrylonitrile and styrene on the central portion.

[0034] The rubber polymer component constituting the core improves impact resistance, particularly at low temperatures, and the shell component can lower interfacial tension and improve adhesive strength at the interface.

[0035] According to one embodiment, the acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubbery polymer of 200 to 350 nm is produced by adding styrene and acrylonitrile to a butadiene-based rubbery polymer and graft-copolymerizing the polymer by a conventional polymerization method such as emulsion polymerization or bulk polymerization.

[0036] The butadiene-based rubbery polymer may be selected from the group consisting of butadiene rubbery polymers, butadiene-styrene rubbery polymers, butadiene-acrylonitrile rubbery polymers, butadiene-acrylate rubbery polymers, and mixtures thereof.

[0037] The acrylonitrile-butadiene-styrene graft copolymer having an average particle diameter of the rubber polymer of 200 to 350 nm may have an average particle diameter of the butadiene-based rubber polymer of, for example, 200 to 350 nm, for example, 250 to 350 nm. When the above range is satisfied, the thermoplastic resin composition can ensure excellent impact resistance and appearance properties.

[0038] The butadiene-based rubber polymer core is contained in an amount of 40 to 70% by weight relative to 100% by weight of the acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm. Meanwhile, the shell may be a styrene-acrylonitrile copolymer copolymerized from a monomer mixture in which the weight ratio of the styrene and the acrylonitrile is 6:4 to 8:2.

[0039] The acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm can be contained in an amount of 20 to 30% by weight, for example, 25 to 30% by weight, relative to 100% by weight of the base resin.

[0040] When the acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 nm to 350 nm in the base resin is less than 20% by weight, it is difficult to achieve excellent impact resistance, and when it exceeds 30% by weight, there is a risk of a decrease in heat resistance and fluidity.

[0041] (B) Styrene-vinyl cyanide copolymer In one embodiment, the styrene-vinyl cyanide copolymer has the function of improving the flowability of the thermoplastic resin composition and maintaining a certain level of compatibility between the components.

[0042] In one embodiment, the styrene-vinyl cyanide copolymer may be a copolymer of styrene and a vinyl cyanide compound. Specifically, the styrene-vinyl cyanide copolymer may be a copolymer of a monomer mixture containing styrene and a vinyl cyanide compound.

[0043] The styrene-vinyl cyanide copolymer can be utilized such that its weight average molecular weight is 80,000 g / mol or more, for example, 85,000 g / mol or more, for example, 90,000 g / mol or more, and for example, 200,000 g / mol or less, for example, 150,000 g / mol or less, for example, 80,000 to 200,000 g / mol, for example, 80,000 to 150,000 g / mol.

[0044] In the present invention, the weight average molecular weight is measured by dissolving a powder sample in tetrahydrofuran (THF) and then using a 1200 series gel permeation chromatography (GPC) manufactured by Agilent Technologies (the column used was LF-804 manufactured by Shodex Corporation, and the standard sample was polystyrene manufactured by Shodex Corporation).

[0045] The vinyl cyanide compound may be one or more selected from acrylonitrile, methacrylonitrile, and fumaronitrile.

[0046] The styrene-derived component is contained in the styrene-vinyl cyanide copolymer in an amount of, for example, 60% by weight or more, for example, 65% by weight or more, for example, 70% by weight or more, for example, 80% by weight or less, for example, 75% by weight or less, for example, 60 to 80% by weight, for example, 65 to 75% by weight, relative to 100% by weight of the styrene-vinyl cyanide copolymer.

[0047] Furthermore, relative to 100% by weight of the styrene-vinyl cyanide copolymer, the component derived from the vinyl cyanide compound is contained in an amount of, for example, 20% by weight or more, such as 25% by weight or more, for example, 40% by weight or less, such as 35% by weight or less, for example, 20 to 40% by weight, for example, 25 to 35% by weight.

[0048] In one embodiment, the styrene-vinyl cyanide copolymer may be a styrene-acrylonitrile copolymer (SAN).

[0049] In one embodiment, the styrene-vinyl cyanide copolymer is included in an amount of 10 to 30% by weight, for example 10 to 25% by weight, based on 100% by weight of the base resin.

[0050] If the content of the styrene-vinyl cyanide copolymer is less than 10% by weight, the moldability of the thermoplastic resin composition may decrease, whereas if it exceeds 30% by weight, the mechanical properties of a molded product using the thermoplastic resin composition may decrease.

[0051] (C) α-Methylstyrene copolymer In one embodiment, the (C) α-methylstyrene-based copolymer can improve the heat resistance of the thermoplastic resin composition.

[0052] In one embodiment, the α-methylstyrene copolymer may be a copolymer of a monomer mixture containing 50 to 80% by weight of α-methylstyrene. In one embodiment, the α-methylstyrene copolymer may be a copolymer of a monomer mixture containing 50 to 80% by weight of α-methylstyrene, 10 to 40% by weight of a vinyl cyanide compound, and 0 to 40% by weight of an aromatic vinyl compound.

[0053] In the α-methylstyrene copolymer, the aromatic vinyl compound may be selected from the group consisting of styrene (excluding α-methylstyrene) substituted or unsubstituted with a halogen or an alkyl group having 1 to 10 carbon atoms, and combinations thereof, and the vinyl cyanide compound may be selected from the group consisting of acrylonitrile, methacrylonitrile, fumaronitrile, and combinations thereof.

[0054] In one embodiment, the α-methylstyrene-based copolymer may be a copolymer of a monomer mixture containing 50 to 80% by weight of α-methylstyrene, 10 to 40% by weight of acrylonitrile, and 0 to 40% by weight of styrene, i.e., an α-methylstyrene-styrene-acrylonitrile copolymer.

[0055] In one embodiment, the weight average molecular weight of the α-methylstyrene-based copolymer may be, for example, 80,000 to 250,000 g / mol, for example, 100,000 to 250,000 g / mol, for example, 100,000 to 200,000 g / mol.

[0056] In one embodiment, the α-methyl styrene based copolymers are produced using conventional manufacturing methods such as emulsion polymerization, suspension polymerization, solution polymerization, and bulk polymerization.

[0057] In one embodiment, the α-methylstyrene copolymer is contained in an amount of 30% by weight or more, for example 50% by weight or less, for example 30 to 50% by weight, for example 30 to 45% by weight, based on 100% by weight of the base resin.

[0058] When the content of the α-methylstyrene copolymer in the base resin satisfies the above-mentioned range, the heat resistance can be significantly improved while maintaining a balance with other physical properties such as mechanical properties and moldability of the thermoplastic resin composition, and molded products produced using this composition can also exhibit excellent heat resistance.

[0059] On the other hand, if the α-methylstyrene copolymer in the base resin is less than 30% by weight, the heat resistance of the thermoplastic resin composition may decrease, and if it exceeds 50% by weight, the impact resistance and appearance properties of the thermoplastic resin composition may decrease.

[0060] (D) an acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm; In one embodiment, (D) an acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm imparts excellent impact resistance and low optical properties to the thermoplastic resin composition.

[0061] The acrylonitrile-butadiene-styrene copolymer resin, in which the rubber polymer has an average particle size of 1,000 to 5,000 nm, may include a core-shell structured dispersed phase including a core made of a butadiene-based rubber polymer and a shell formed by graft polymerization of acrylonitrile and styrene onto the core, and a continuous phase of a styrene-acrylonitrile copolymer.

[0062] The acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubbery polymer of 1,000 to 5,000 nm can be produced by suspension or bulk polymerization of three components, namely, a butadiene-based rubbery polymer, acrylonitrile, and styrene.

[0063] The styrene-acrylonitrile copolymer forming the continuous phase of the styrene-acrylonitrile copolymer may be a non-branched linear styrene-acrylonitrile copolymer.

[0064] The butadiene-based rubbery polymer may be selected from the group consisting of butadiene rubbery polymers, butadiene-styrene rubbery polymers, butadiene-acrylonitrile rubbery polymers, butadiene-acrylate rubbery polymers, and mixtures thereof.

[0065] The acrylonitrile-butadiene styrene copolymer resin in which the rubber polymer has an average particle size of 1,000 to 5,000 nm may have an average particle size of, for example, 1,000 to 5,000 nm, such as 1,000 to 4,000 nm, for example, 2,000 to 4,000 nm.

[0066] The unbranched linear styrene-acrylonitrile copolymer forming the continuous phase may have a weight average molecular weight of, for example, 50,000 to 250,000 g / mol, for example, 50,000 to 200,000 g / mol, for example, 50,000 to 150,000 g / mol.

[0067] Based on 100% by weight of the base resin, the acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm may be contained in an amount of 10% by weight or more, for example, 30% by weight or less, for example, 10 to 30% by weight, for example, 15 to 30% by weight.

[0068] On the other hand, based on 100% by weight of the acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm, the core-shell structured dispersed phase may be contained in an amount of 10 to 30% by weight, and the styrene-acrylonitrile copolymer (a non-branched linear styrene-acrylonitrile copolymer) continuous phase may be contained in an amount of 70 to 90% by weight.

[0069] When the acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm in the thermoplastic resin composition is less than 10% by weight, the impact resistance and low optical properties of the thermoplastic resin composition may be reduced, and when it exceeds 30% by weight, the mechanical properties of the thermoplastic resin composition may be reduced.

[0070] (E) Polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer In one embodiment, the polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer (E) reduces the friction coefficient of a thermoplastic resin composition and a molded article using the same, while improving the durability of the reduction in frictional noise, thereby exhibiting excellent frictional noise reduction properties.

[0071] In one embodiment, the polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer may be a substituted or unsubstituted polyolefin backbone grafted with an aromatic vinyl-glycidyl (meth)acrylate copolymer.

[0072] The substituted or unsubstituted polyolefin may be one or more selected from the group including polyethylene and ethylene-vinyl acetate copolymer. The ethylene-vinyl acetate copolymer may be a copolymer of ethylene and vinyl acetate.

[0073] The aromatic vinyl-glycidyl (meth)acrylate copolymer grafted onto the polyolefin backbone may be a copolymer of an aromatic vinyl compound and glycidyl (meth)acrylate.

[0074] The aromatic vinyl compound may be any one or more selected from styrene, alkyl-substituted styrenes having 1 to 10 carbon atoms, halogen-substituted styrenes, vinyl toluene, vinyl naphthalene, and mixtures thereof. Specific examples of the alkyl-substituted styrenes include α-methylstyrene, p-methylstyrene, o-ethylstyrene, m-ethylstyrene, p-ethylstyrene, pt-butylstyrene, and 2,4-dimethylstyrene.

[0075] As the glycidyl (meth)acrylate, any one or more selected from glycidyl acrylate, glycidyl methacrylate, and a mixture thereof can be used.

[0076] Examples of the aromatic vinyl-glycidyl methacrylate copolymer include copolymers of styrene and glycidyl acrylate, copolymers of styrene and glycidyl methacrylate, copolymers of α-methylstyrene and glycidyl acrylate, copolymers of α-methylstyrene and glycidyl methacrylate, copolymers of styrene, α-methylstyrene and glycidyl acrylate, copolymers of styrene, α-methylstyrene and glycidyl methacrylate, copolymers of styrene, α-methylstyrene and glycidyl methacrylate, or copolymers of styrene, α-methylstyrene, glycidyl acrylate and glycidyl methacrylate, and preferably copolymers of styrene-glycidyl methacrylate.In this case, the styrene-glycidyl methacrylate copolymer may be a copolymer of a monomer mixture containing 50-95% by weight of styrene and 5-50% by weight of glycidyl methacrylate.

[0077] As an example, the polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer may be one or more selected from the group including polyethylene-styrene-glycidyl methacrylate graft copolymer (PE-g-SGMA) and ethylene-vinyl acetate-styrene-glycidyl methacrylate graft copolymer (EVA-g-SGMA).

[0078] In one embodiment, based on 100% by weight of the polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer, the copolymer may contain 70 to 95% by weight of the substituted or unsubstituted polyolefin and 5 to 30% by weight of the aromatic vinyl-glycidyl (meth)acrylate copolymer.

[0079] The polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer may be contained in an amount of, for example, 1 to 6 parts by weight, for example, 2 to 6 parts by weight, for example, 2 to 5 parts by weight, relative to 100 parts by weight of the base resin. When the polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer is contained in an amount of less than 1 part by weight relative to 100 parts by weight of the base resin, the friction noise reduction characteristics of the molded product using the copolymer are unlikely to be exhibited, and when the amount exceeds 6 parts by weight, mechanical properties such as rigidity may be reduced.

[0080] (F) Other additives In addition to the components (A) to (E), the thermoplastic resin composition according to one embodiment may further include one or more additives required for achieving a balance between the various physical properties under conditions for maintaining excellent frictional noise reduction effects, low optical properties, and mechanical properties, or depending on the end use of the thermoplastic resin composition.

[0081] Specifically, examples of the additives that can be used include nucleating agents, coupling agents, fillers, plasticizers, lubricants, release agents, antibacterial agents, heat stabilizers, antioxidants, UV stabilizers, flame retardants, antistatic agents, colorants, and impact modifiers. These can be used alone or in combination of two or more.

[0082] These additives are appropriately included within a range that does not impair the physical properties of the thermoplastic resin composition. Specifically, they may be included in an amount of 20 parts by weight or less per 100 parts by weight of the base resin, but are not limited to this amount.

[0083] The thermoplastic resin composition according to the present invention is produced by a known method for producing a thermoplastic resin composition.

[0084] For example, the thermoplastic resin composition according to the present invention can be prepared in the form of pellets by simultaneously mixing the components of the present invention and other additives and then melt-kneading them in an extruder.

[0085] A molded article according to one embodiment of the present invention is produced from the thermoplastic resin composition described above.

[0086] The thermoplastic resin composition has excellent friction noise reduction effect, low optical properties, and mechanical properties, and is therefore widely applicable to various products used with or without painting, and in particular, since it minimizes the stick-slip phenomenon, it is usefully applied to applications such as interior materials for automobiles, for example, electric automobiles, which require a large reduction in friction noise. In addition, when the molded product is used, it is possible to provide more sophisticated automobile interior materials, etc., based on the excellent low optical properties of the thermoplastic resin according to one embodiment. EXAMPLES

[0087] The present invention will be described in more detail below through examples and comparative examples. However, the following examples and comparative examples are for illustrative purposes only and are not intended to limit the present invention.

[0088] Example 1, Example 2, and Comparative Examples 1 to 4 The thermoplastic resin compositions of Examples 1 and 2 and Comparative Examples 1 to 4 were produced according to the content ratios of the components shown in Table 1 below.

[0089] In Table 1, (A), (B), (C), and (D) are contained in the base resin and are shown in weight percent based on the total weight of the base resin, and (E) and (E') are added to the base resin and are shown in parts by weight based on 100 parts by weight of the base resin.

[0090] The components listed in Table 1 were dry mixed and quantitatively and continuously fed into the feed section of a twin-screw extruder (L / D=36, Φ=45mm) and melted / kneaded. Next, the thermoplastic resin composition pelletized by the twin-screw extruder was dried at about 80°C for about 4 hours, and then a test piece for evaluating mechanical properties and low optical properties and a test piece for evaluating squeak noise measuring 100mm x 100mm x 3.2mm (width x length x thickness) were produced using a 6oz injection molding machine with a cylinder temperature of about 220°C and a mold temperature of about 60°C.

[0091] [Table 1]

[0092] The explanation of each configuration listed in Table 1 above is as follows.

[0093] (A) An acrylonitrile-butadiene-styrene graft copolymer having an average particle size of the rubber polymer of 200 to 350 nm. An acrylonitrile-butadiene-styrene graft copolymer (manufactured by Lotte Advanced Materials Co., Ltd.) comprising approximately 58% by weight of a core (average particle size: approximately 250 nm) made of a butadiene rubber polymer, and a shell formed by graft polymerizing acrylonitrile and styrene onto the core.

[0094] (B) Styrene-vinyl cyanide copolymer A styrene-acrylonitrile copolymer (manufactured by Lotte Advanced Materials) having a weight average molecular weight of approximately 110,000 g / mol, copolymerized from a monomer mixture containing approximately 28% by weight of acrylonitrile and approximately 72% by weight of styrene.

[0095] (C) α-Methylstyrene copolymer An α-methylstyrene-styrene-acrylonitrile copolymer (manufactured by Lotte Advanced Materials Co., Ltd.) having a weight average molecular weight of approximately 120,000 g / mol, copolymerized from a monomer mixture containing approximately 19% by weight of styrene, approximately 27% by weight of acrylonitrile, and approximately 54% by weight of α-methylstyrene.

[0096] (D) an acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer of 1,000 to 5,000 nm; An acrylonitrile-butadiene-styrene copolymer resin (manufactured by Lotte Advanced Materials Co., Ltd.) having a core-shell structure with a core made of a butadiene rubber polymer having an average particle size of approximately 3,000 nm and a shell made of a styrene-acrylonitrile copolymer, the dispersed phase being approximately 16% by weight, and a continuous phase made of a styrene-acrylonitrile copolymer (a non-branched linear styrene-acrylonitrile copolymer having a weight average molecular weight of approximately 70,000 g / mol) being approximately 84% by weight.

[0097] (E) Polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer Polyethylene-styrene-glycidyl methacrylate graft copolymer (PE-g-SGMA, manufactured by NOF), in which styrene-glycidyl methacrylate copolymer is grafted onto the polyethylene main chain.

[0098] (E') Dimethylpolysiloxane Dimethylpolysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) with a kinematic viscosity of approximately 100 cSt at 25°C.

[0099] Experimental Example The experimental results are shown in Table 3 below.

[0100] (1) Tensile strength (MPa): The tensile strength of test pieces for evaluating mechanical properties was measured based on ISO 527-1.

[0101] (2) Flexural strength (MPa): The flexural strength of the test specimen for evaluating mechanical properties was measured in accordance with ISO 178.

[0102] (3) Flexural modulus (MPa): The flexural modulus of the test specimen for evaluating mechanical properties was measured in accordance with ISO 178.

[0103] (4) Impact resistance (kJ / m 2 ): The notched Izod impact strength of the test specimens for evaluating mechanical properties was measured based on ISO 180.

[0104] (5) Low Optical Properties (GU): Gloss was measured at an angle of 20° based on ASTM D523.

[0105] (6) Squeak noise: Based on VDA230-206, friction noise of test pieces for evaluating squeak noise corresponding to the following condition 1 (normal temperature condition) and condition 2 (severe condition) was measured.

[0106] - Condition 1 (room temperature condition): The test piece is left at room temperature without any additional heat treatment. -Condition 2 (harsh conditions): The test piece was left in an oven at approximately 80°C for approximately 300 hours. Figure 1 is a diagram of the basic principle of VDA 230-206. Referring to Figure 1, material A and material B are the same material heat-treated under the same conditions, and material A, which is the mobile phase, moves relative to material B by a spring component. The force F applied by the spring component to each other is N is 40N, and the moving speed of the sliding carriage is V s The velocity was 4 mm / s, and the contact area of ​​the two material specimens was 1,250 mm 2 The spring movement phenomenon was due to stick and slip, and this was used to evaluate the creaking noise.

[0107] Table 2 below shows the evaluation criteria for squeak noise; the closer the RPN is to 1, the better the effect of reducing friction noise.

[0108] [Table 2]

[0109] Referring to Table 2, RPN1-3 means that there is almost no noise, RPN4-5 means that the noise is at the limit and cannot be eliminated by the stick-slip effect, and RPN6-10 means that the stick-slip effect is obvious and noise is always present.

[0110] [Table 3]

[0111] From Tables 1 and 3 above, it was confirmed that by using the acrylonitrile-butadiene-styrene graft copolymer, the styrene-vinyl cyanide copolymer, the α-methylstyrene copolymer, the acrylonitrile-butadiene-styrene copolymer resin, and the polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer in optimal amounts as in Examples 1 and 2, it is possible to provide a thermoplastic resin composition exhibiting superior friction noise reduction effect, mechanical properties (impact resistance and rigidity), and low optical properties compared to the comparative examples, as well as a molded product using the same.

[0112] Although the present invention has been described above through the above-mentioned preferred embodiment, it will be easily understood by those skilled in the art to which the present invention pertains that the present invention is not limited thereto, and various modifications and variations are possible without departing from the concept and scope of the claims set forth below.

Claims

1. (A) 20 to 30% by weight of an acrylonitrile-butadiene-styrene graft copolymer having an average particle size of a rubber polymer of 200 to 350 nm; (B) 10 to 30% by weight of a styrene-vinyl cyanide copolymer; (C) 30 to 50% by weight of an α-methylstyrene-styrene-acrylonitrile copolymer having a weight average molecular weight of 100,000 to 200,000 g / mol; and (D) 10 to 30% by weight of an acrylonitrile-butadiene-styrene copolymer resin having an average particle size of a rubber polymer of 1,000 to 5,000 nm; For 100 parts by weight of the base resin, (E) 1 to 6 parts by weight of a polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer; The acrylonitrile-butadiene-styrene copolymer resin (D), in which the average particle diameter of the rubber polymer is 1,000 to 5,000 nm, comprises a dispersed phase having a core-shell structure including a core made of a butadiene-based rubber polymer and a shell formed by graft-polymerizing acrylonitrile and styrene onto the core, and a continuous phase of a styrene-acrylonitrile copolymer. Thermoplastic resin composition.

2. The acrylonitrile-butadiene-styrene graft copolymer (A) having an average particle size of the rubber polymer of 200 to 350 nm is A core made of a butadiene-based rubber polymer, and 2. The thermoplastic resin composition according to claim 1, which has a core-shell structure including a shell formed by graft polymerization of acrylonitrile and styrene onto the core.

3. The thermoplastic resin composition according to claim 2, comprising 40 to 70% by weight of the core based on 100% by weight of the acrylonitrile-butadiene-styrene graft copolymer (A) having an average particle size of 200 to 350 nm.

4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein the (B) styrene-vinyl cyanide copolymer is a copolymer of a monomer mixture containing 60 to 80% by weight of styrene and 20 to 40% by weight of a vinyl cyanide compound.

5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein the weight average molecular weight of the styrene-vinyl cyanide copolymer (B) is 80,000 to 200,000 g / mol.

6. The (C) α-methylstyrene-styrene-acrylonitrile copolymer is a copolymer of a monomer mixture containing 50 to 80% by weight of α-methylstyrene, 10 to 40% by weight of acrylonitrile, and more than 0% by weight and 40% by weight or less of styrene. The thermoplastic resin composition according to any one of claims 1 to 5.

7. Based on 100% by weight of the acrylonitrile-butadiene-styrene copolymer resin having an average particle size of the rubber polymer (D) of 1,000 to 5,000 nm, The thermoplastic resin composition according to any one of claims 1 to 6, comprising 10 to 30% by weight of the dispersed phase of the core-shell structure and 70 to 90% by weight of the continuous phase of the styrene-acrylonitrile copolymer.

8. The polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer (E) is a substituted or unsubstituted polyolefin main chain to which an aromatic vinyl-glycidyl (meth)acrylate copolymer is grafted. The thermoplastic resin composition according to any one of claims 1 to 7.

9. Based on 100% by weight of the (E) polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer, 70 to 95% by weight of said substituted or unsubstituted polyolefin; Contains 5 to 30% by weight of the aromatic vinyl-glycidyl (meth)acrylate copolymer; The thermoplastic resin composition according to claim 8.

10. The thermoplastic resin composition according to claim 8 or 9, wherein the substituted or unsubstituted polyolefin is at least one selected from the group consisting of polyethylene and ethylene-vinyl acetate copolymer.

11. The thermoplastic resin composition according to any one of claims 8 to 10, wherein the aromatic vinyl-glycidyl (meth)acrylate copolymer is a styrene-glycidyl methacrylate copolymer.

12. The styrene-glycidyl methacrylate copolymer is 50 to 95% by weight of styrene, and The thermoplastic resin composition according to claim 11, which is a copolymer of a monomer mixture containing 5 to 50% by weight of glycidyl methacrylate.

13. The thermoplastic resin composition according to any one of claims 1 to 12, wherein the (E) polyolefin-aromatic vinyl-glycidyl (meth)acrylate graft copolymer is at least one selected from the group consisting of polyethylene-styrene-glycidyl methacrylate graft copolymer and ethylene-vinyl acetate-styrene-glycidyl methacrylate graft copolymer.

14. The thermoplastic resin composition according to any one of claims 1 to 13, further comprising at least one additive selected from the group consisting of nucleating agents, coupling agents, fillers, plasticizers, lubricants, release agents, antibacterial agents, heat stabilizers, antioxidants, UV stabilizers, flame retardants, antistatic agents, colorants, and impact modifiers.

15. A molded article comprising the thermoplastic resin composition according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Motor vehicle trim parts

    JP1988152659A

  • Thermoplastic resin composition

    JP1992314750A

  • Thermoplastic molding composition

    JP1992332742A

  • Thermoplastic resin composition and molded product

    JP2008056904A

  • Method for producing thermoplastic resin composition

    JP2015218309A